Five-star basketball presents my favorite moves (Wish Pub., 2003)
Five-Star Basketball, the long-time leader in basketball instruction, has teamed up with six of the greatest professional women players to bring young players everywhere a state-of-the-art drill book like no other. Each chapter of the book breaks down a different star player's skills. Those skills are analysed by the player herself, her peers and the elite basketball experts of the Five-Star Camps. Then, the book provides a selection of drills, games and practice regimes that focus on developing those skills